Pemanfaatan Tiktok Sebagai Media Komunikasi Informasi Di Kalangan Generasi Z: Studi Kasus Konten Edukatif Tiktok - Rina Devi Azizah; Anak Agung Ayu Zahra Laylia Cantika; Amellya Febryanti Irawan (CV. ITTC INDONESIA, 2026)
This study aims to analyze the use of TikTok as a medium for communicating information among Generation Z, with a focus on educational content produced on the platform. TikTok, as one of the most popular social media applications among young people, offers various forms of content that can influence how users receive and disseminate information. This study uses a qualitative approach with a case study design to analyze the use of TikTok as a medium for information communication among Generation Z through educational content. Primary data was obtained from educational video content uploaded on the TikTok platform. Secondary data was obtained from scientific journal articles, books, and academic publications related to social media, information communication, TikTok, and Generation Z. The results of the study show that the use of TikTok as a means of non-formal education indicates that social media has great potential in supporting the learning process and dissemination of information in the digital age. On the other hand, the effectiveness of TikTok as a medium for information communication is highly dependent on the quality of the content and the digital literacy skills of its users. Therefore, continuous efforts are needed to encourage the production of accurate, ethical, and responsible educational content, as well as to strengthen Generation Z's critical awareness in filtering information.